A 1.9‐Ga Mélange Along the Northern Margin of the North China Craton: Implications for the Assembly of Columbia Supercontinent. Issue 10 (15th October 2018) - Wu, Chen; Zhou, Zhiguang; Zuza, Andrew V.; Wang, Guosheng; Liu, Changfeng; Jiang, Tian
Abstract: The involvement and location of the Neoarchean‐Paleoproterozoic North China craton in the supercontinent Columbia remains enigmatic, and the tectonic history along its margins impacts our understanding of connections between North China and other continents. Here we present structural observations from a Paleoproterozoic mélange that is located along its northern margin and that we refer to as the Bayan Obo mélange. It is composed of a structurally complex tectonic mixture of metapelites and metasedimentary rocks mixed with exotic blocks of ultramafic‐mafic rocks, metabasalts, metacarbonate and alkaline rocks, and tonalite‐trondhjemite gneisses. New zircon geochronology of the various constituent blocks suggest that it formed, and was subsequently deformed, at ca. 1.9 Ga. The oldest intramélange blocks are 2.45‐ to 2.54‐Ga tonalite‐trondhjemite‐granodiorite rocks and granitoids that signify the stabilization of the northern North China in the Neoarchean‐Paleoproterozoic. A ca. 2.45‐Ga plagiogranite block probably originated by partial melting of the older tonalite‐trondhjemite‐granodiorite rocks. We suggest that this mélange formed in a sedimentary setting near the subduction trench, on the basis of mixing of upper and lower plate volcanic rocks and textural relationships. The Bayan Obo mélange thus represents one of the oldest documented sedimentary mélanges on Earth, yet its fundamental characteristics strongly resemble Phanerozoic subduction complexes. Based on similar ages and styles of deformation, this zone may represent the ca. 1.9‐Ga collisional zone between North China and the southwestern margin of the Siberia craton. In this context, the North China craton became an integral component of the supercontinent Columbia starting at ca. 1.9 Ga. Plain Language Summary: The Paleoproterozoic‐Archean North China craton is one of the oldest cratons on Earth. Understanding its tectonic evolution history can provide better constraints on the assembly and tectonic evolution of the Paleoproterozoic‐Mesoproterozoic Columbia supercontinent. In addition, establishing its tectonic evolution will help to affect our current understanding of the Proterozoic‐Phanerozoic formation history of Asia. In a general sense, understanding the formation processes and significance of mélange associated with collision‐accretion in the geological record is significant in documenting the tectonic evolution of orogenic belts. In this study, we report for the first time a new Paleoproterozoic mélange located in the Bayan Obo region on the northernmost margin of the North China craton (present‐day coordinates). This mélange zone was formed and subsequently deformed and metamorphosed at ca. 1.9 Ga. Our observations across this zone are consistent with the proposal that North China collided with the southern margin of the Siberia craton at this time, which has a similar accretionary wedge. It is should be considered that the North China craton was beginning to the context of the Columbia from ca. 1.9 Ga. Key Points: The Bayan Obo sedimentary mélange formed and deformed along the northern margin of the North China craton at ca. 1.9 Ga North China collided with the southern margin of the Siberia craton at ca. 1.9 Ga, which has a similar accretionary wedge The North China craton's involvement in the Columbia supercontinent started at ca. 1.9 Ga